La necesidad de tipificar como delito al contagio doloso del síndrome de inmuno deficiencia adquirida (sida), en el código orgánico integral penal del Ecuador - Ochoa Romero, Karina Cecibel (2016)
The current social reality of Ecuador, presents highly troubling aspects regarding the criminal behavior of people, because in the last days; They have been observed in different mass media, headlines and reports about highly harmful behaviors for many citizens, involving the intentional transmission as serious as AIDS diseases through such treacherous and malicious procedures such as intentional punctures with needles or other sharp objects containing contaminated blood. The Ecuadorian Criminal Code of Integral does not establish any penalty for an offense suppress the spread of Human Immunodeficiency Virus (HIV) which causes Acquired Immune Deficiency Syndrome (AIDS), when the carrier individual knowing of his illness, with the intention of causing damage to other people maliciously transmitted using any means for propagation It is therefore necessary to regulate this reality that is currently suffers from lack of rules in the Penal Law, in this way be achieved curb abuse of injustice and inequality before the law to protect the dignity, integrity and security, as we guaranteed by our Constitution of the Republic of Ecuador.